PlatFab: A Platform Engineering Approach to Improve Developer Productivity - Srinivasan, Vaishnavi; Rajkumar, Manimegalai; Santhanam, Srivatsan; Garg, Arjit (Journal of Information Systems Engineering and Business Intelligence, 2025)
Background: Software developers are key players in IT/ITES business in order to drive software development by writing high-quality code quickly. Based on user needs, they must adapt evolving technologies and tools to produce efficient and successful software using Software Development Life Cycle (SDLC) principles. Platform Engineering comprises a set of activities to design, develop and maintain software code, making it a foundation for building software applications. Objective: This work focuses on reducing the time and effort needed to execute the above tasks that boosts software developer productivity which includes software development workflow automation. The main objective of the proposed work is to lower total cost of ownership, standardize software development practices, help cost optimization and reduce production incidents. Methods: PlatFab, a Platform Engineering service implemented in Industrial Budgeting System is presented in this work. The methodology involves custom developer portal with Continuous Integration and Continuous Delivery/Continuous Deployment. (CI/CD) pipeline to automate financial workflows and streamline collaborative development. It provides the developers architectural components, containers, infrastructure automation and services orchestration that helps them to concentrate on their quality code irrespective of implementation efforts. Results: After deploying PlatFab in an organization's software development, build time is reduced by one minute for each service, and 60MB of storage space is saved for each service. Developers can handle vulnerability attacks in one day. Before the use of PlatFab, build time was five minutes, 2 GB was used for each service, and vulnerability handling required five days to resolve. Production downtime issues were 12 before PlatFab and were reduced to almost zero after integrating PlatFab. Conclusion: The results after implementing PlatFab for a Budgeting System service in an IT Organization help the developers reduce build time, number of days to fix vulnerabilities, and space requirements for the service. PlatFab helps the developers complete their projects with quality code in a shorter time, improving their productivity. Keywords: Agile Methodology, Budgeting Service, Platform Engineering, Software Development Life Cycle, Service Oriented Architecture.